2013
DOI: 10.1142/s2010194513010155
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Diopside by Solution Combustion Process Using Glycine Fuel

Abstract: Nano ceramic Diopside ( CaMgSi 2 O 6) powders are synthesized by Solution Combustion Process(SCS) using Calcium nitrate, Magnesium nitrate as oxidizer and glycine as fuel, fumed silica as silica source. Ammonium nitrate (AN) is used as extra oxidizer. Effect of AN on Diopside phase formation is investigated. The adiabatic flame temperatures are calculated theoretically for varying amount of AN according to thermodynamic concept and correlated with the observed flame temperatures. A “Multi channel thermocouple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…During synthesis of V 2 O 5 by SCS, though the ignition temperature is maintained at 500 °C, it is reported that at the microscopic scale the temperature can be as high as 1500 °C. This is achieved at an optimum equivalence ratio of fuel (F, urea) and oxidizer (O, metal nitrate) (defined as oxidizer to fuel ratio; O/F) of unity [41,42]. Due to this effect, the crystallites are well formed, leading to sharp peaks in the XRD pattern.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…During synthesis of V 2 O 5 by SCS, though the ignition temperature is maintained at 500 °C, it is reported that at the microscopic scale the temperature can be as high as 1500 °C. This is achieved at an optimum equivalence ratio of fuel (F, urea) and oxidizer (O, metal nitrate) (defined as oxidizer to fuel ratio; O/F) of unity [41,42]. Due to this effect, the crystallites are well formed, leading to sharp peaks in the XRD pattern.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…SCS is a fast process and it is completed in a few seconds, hence the process can be assumed as adiabatic. Using the thermodynamic data for the reactants and products (Table ), the enthalpy of combustion and the theoretical adiabatic combustion temperatures were calculated by the Equations and : ΔHcomb.=][nnormalΔfnormalproducts][nnormalΔfnormalreactantsQ=ΔH=T0Titalicadfalse(nCpfalse)dT…”
Section: Resultsmentioning
confidence: 99%
“…where ∆ H is the enthalpy of combustion, C p is the heat capacity of products at constant pressure. For simplification in the calculation of exothermic heat, the reaction temperature ( T 0 ) has been assumed to be 623 K, which is approximately the decomposition temperature of urea and T f is the adiabatic combustion temperature …”
Section: Resultsmentioning
confidence: 99%
“…Sol–gel assisted ball milling method was followed to prepare diopside at 1200°C (Najafinezhad et al, ). On the other hand, solution combustion synthesis was employed to obtain pure diopside at 800°C by using glycine and ammonium nitrate as fuel and oxidizer, respectively (Sherikar & Umarji, ).…”
Section: Significance Of Synthesis Techniquesmentioning
confidence: 99%